ANTIDIABETIC ACTIVITY TEST USING AMLA FRUIT (PHYLLANTHUS EMBLICA L) EXTRACT IN ALLOXAN-INDUCED BALB/C MICE - Cahyaningrum, Putu Lakustini; Made Yuliari, Sang Ayu; Suta, Ida Bagus Putra (Journal of Vocational Health Studies, 2019)
Background: The content of secondary metabolites in amla (phyllanthus emblica L.) such as flavonoids and phenols have the potential as an antioxidant. One of the benefits of antioxidants is to prevent degenerative diseases, such as diabetes mellitus. Purpose: This research to determine activity of amla fruit extract in reducing blood glucose levels at balb/c mice induced with alloxan. Method: This research method uses a pre and posttest-controlled group design with 35 balb/c mice divided into five treatments groups. In the positive control group and the treatment group alloxan was injected for 14 days. Result: Amla (Phyllanthus emblica L.) fruit extract at a dose of 40 mg / 20 g BW was equivalent to positive control of glibenclamide dose 3 mg / 20 g BW compared to the treatment group at a dose of 10 mg / 20 g BW and 20 mg /20 g BW. Conclusion: From this research, it was obtained that the best dose of Amla fruit (phylanthus emblica L) extract applied to blood glucose was 40 mg/20mg BW with a decrease percentage of 56,93% with an effective dose value (ED50) 50% of 34.00 mg / 20 g BW.